The Importance of Socio-environmental Problems and their Adequacy in Geography School Textbooks According to the Opinion of Students: La importancia de los problemas socioambientales y su adecuación en los libros de texto de geografía según la opinión del alumnado (Papeles, 2024)
Introducion: Currently, there is a great need to deal with social problems in the school environment in order to create a committed and aware society. However, the lack of a critic problematization in the classroom creates inadequate student learning among students and poor development of geographical thinking. Methodology: The aim of this work is to analyze the social representation of students in the 3rd year of ESO and 2nd year of Baccalaureate (n = 133) (2022-2023) on the importance of socio-environmental problems (natural hazards, pollution, migrations and rural exodus), and the adequacy of these questions in Geography school textbooks. Results: Regarding the results, in general, the students give great importance to these problems and believe that their treatment in the textbooks is adequate. However, it is also corroborated that there are differences between the two courses analyzed, specifically the reasons for the importance of natural risks and in the treatment of rural exodus in the textbooks (most unfavorable opinion according to ESO students). Discussion and Conclusions: To sum up, it is worth noting the importance of dealing with socio-environmental issues to acquire significant learning and create a critical society due to 21st century challenges.
Keywords: Socio-environmental problems; geographical thinking; school geography; social representation; textbooks